2012
DOI: 10.1088/0004-637x/756/2/156
|View full text |Cite
|
Sign up to set email alerts
|

DYNAMICAL EVOLUTION OF VISCOUS DISKS AROUND Be STARS. I. PHOTOMETRY

Abstract: Be stars possess gaseous circumstellar disks that modify in many ways the spectrum of the central B star. Furthermore, they exhibit variability at several timescales and for a large number of observables. Putting the pieces together of this dynamical behavior is not an easy task and requires a detailed understanding of the physical processes that control the temporal evolution of the observables. There is an increasing body of evidence that suggests that Be disks are well described by standard α-disk theory. T… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

27
215
2
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 112 publications
(248 citation statements)
references
References 42 publications
(48 reference statements)
27
215
2
4
Order By: Relevance
“…Rivinius et al 2001). Recently, the spreading out of such discs is also attempted to be understood in terms of viscous evolution (Haubois et al 2012), similarly to what we propose here for the FRMS discs. The formation of stars as opposed to planets in circumstellar discs might seem unusual.…”
Section: Top-heavy Imfsupporting
confidence: 62%
See 1 more Smart Citation
“…Rivinius et al 2001). Recently, the spreading out of such discs is also attempted to be understood in terms of viscous evolution (Haubois et al 2012), similarly to what we propose here for the FRMS discs. The formation of stars as opposed to planets in circumstellar discs might seem unusual.…”
Section: Top-heavy Imfsupporting
confidence: 62%
“…This process is analogous to the equatorial mass loss in Be-type stars (e.g. Rivinius et al 2001;Townsend et al 2004;Haubois et al 2012). In FRMS, the total amount of mass lost by this process is rather high, and it is hardly plausible that the ejected material may immediately leave the vicinity of the star: to lift the material out of the gravitational potential of the parent star, an energy supply at a rate of GMṀ/(2R dd ) is required if the decretion disc is first established at a characteristic radius R dd after being ejected.…”
Section: Equatorial Mass Ejectionsmentioning
confidence: 85%
“…For isothermal Be disks fed at a (nearly) constant rate from the central star, it can be demonstrated that the radial density is a power law with n = 3.5. However, disks either subjected to varying mass feeding rates, or undergoing build-up or dissipation phases, will have much more complex density slopes (Haubois et al 2012), which are here simulated by allowing n to be a free parameter.…”
Section: The Disk Brightness Profilementioning
confidence: 99%
“…The original source of this classification is unclear, but since that the star shows several Be-star typical outbursts (see Fig. 1 vs. Haubois et al 2012, for a theoretical model how such outbursts produce the observed light curve) there is no strong reason to doubt the classification.…”
Section: Hd 186567 (Kic 11971405)mentioning
confidence: 99%